Responses to Targets in the Visual Periphery in Deaf and Normal-Hearing Adults. - Rothpletz, Ann M.; Ashmead, Daniel H.; Tharpe, Anne Marie (Journal of Speech, Language & Hearing Research, 2003)
The purpose of this study was to compare the response times of deaf and normal-hearing individuals to the onset of target events in the visual periphery in distracting and nondistracting conditions. Visual reaction times to peripheral targets placed at 3 eccentricities to the left and right of a center fixation point were measured in prelingually deafened adults and normal-hearing adults. Deaf participants responded more slowly than normal-hearing participants to targets in the near periphery in the nondistracting condition and to targets in the near and distant periphery when distracting stimuli were present. One interpretation of these findings is that deaf individuals may be more deliberate than normal-hearing individuals in responding to near peripheral events and to peripheral events that occur in the presence of distracting stimuli. Reprinted by permission of the publisher.